Penile aseptic abscess in the cavernous body at the base of the penis: a case report - Xia Man-Cheng; Yin Ke-Qiang; Wang Yu-Sheng; Chen Jia-Wei; Bian Xiao-Dong; Shuang Wei-Bing (Sciendo, 2021)
We report a case of aseptic abscess in the cavernous body at the base of the penis. In our clinical observation, the patient underwent puncture and drainage of the corpus cavernosum abscess, followed by surgical resection of the abscess wall, with the incisions closed layer by layer with primary suture. In addition, we paid attention to strengthening the postoperative management by using elastic bandages to wrap the penis intermittently to prevent edema; the incision would not be covered with dressings from the third day after the operation, so as to keep the incision site dry in an open way. During the period of indwelling of the catheter after the operation, we noticed the care of the external orifice of the urethra to reduce the occurrence of catheter-related infections. Finally, the patient was diagnosed with a penile aseptic abscess in the cavernous body at the base of the penis. The patient recovered well after surgery and was discharged 1 week later. At 1.5 years after the operation, the shape of the penis returned to normal, and the erectile function was normal. It was seen that good nursing concept is of great help for prognosis, which could avoid infection and edema, and is conducive to wound healing.